Intravenous and oral copper kinetics, biodistribution and dosimetry in healthy humans studied by [64Cu]copper PET/CT - Kristoffer Kjærgaard; Thomas Damgaard Sandahl; Kim Frisch; Karina Højrup Vase; Susanne Keiding; Hendrik Vilstrup; Peter Ott; Lars Christian Gormsen; Ole Lajord Munk (SpringerOpen, 2020)
Abstract Purpose Copper is essential for enzymatic processes throughout the body. [64Cu]copper (64Cu) positron emission tomography (PET) has been investigated as a diagnostic tool for certain malignancies, but has not yet been used to study copper homeostasis in humans. In this study, we determined the hepatic removal kinetics, biodistribution and radiation dosimetry of 64Cu in healthy humans by both intravenous and oral administration. Methods Six healthy participants underwent PET/CT studies with intravenous or oral administration of 64Cu. A 90 min dynamic PET/CT scan of the liver was followed by three whole-body PET/CT scans at 1.5, 6, and 20 h after tracer administration. PET data were used for estimation of hepatic kinetics, biodistribution, effective doses, and absorbed doses for critical organs. Results After intravenous administration, 64Cu uptake was highest in the liver, intestinal walls and pancreas; the gender-averaged effective dose was 62 ± 5 μSv/MBq (mean ± SD). After oral administration, 64Cu was almost exclusively taken up by the liver while leaving a significant amount of radiotracer in the gastrointestinal lumen, resulting in an effective dose of 113 ± 1 μSv/MBq. Excretion of 64Cu in urine and faeces after intravenous administration was negligible. Hepatic removal kinetics showed that the clearance of 64Cu from blood was 0.10 ± 0.02 mL blood/min/mL liver tissue, and the rate constant for excretion into bile or blood was 0.003 ± 0.002 min− 1. Conclusion 64Cu biodistribution and radiation dosimetry are influenced by the manner of tracer administration with high uptake by the liver, intestinal walls, and pancreas after intravenous administration, while after oral administration, 64Cu is rapidly absorbed from the gastrointestinal tract and deposited primarily in the liver. Administration of 50 MBq 64Cu yielded images of high quality for both administration forms with radiation doses of approximately 3.1 and 5.7 mSv, respectively, allowing for sequential studies in humans. Trial registration number EudraCT no. 2016-001975-59. Registration date: 19/09/2016.